PENGARUH PENAMBAHAN BIOIMUN EKSTRAK TERONG ASAM-LEMPUYANG TERHADAP PERTUMBUHAN IKAN KAKAP PUTIH (Lates calcarifer) - M. Bahrus Syakirin; Tri Yusufi Mardiana; Tri Murni Sekarsari; Ashari Fahrurozi (Jurnal Perikanan Unram, 2024)
White sea bass (Lates calcalifer) is a fish commodity that has high economic value. Generally, the problems with sea bass production are the high price of feed and lack of feed efficiency. The need for efficiency efforts in feed can be done by adding natural supplements to feed white sea bass. The aim of the research was to determine the effect of adding bio-immune to feed on growth and the best dose. The research results show a very real difference in influence. Providing bio-immune at a dose of 10 ml/1 kg of feed provided an increase in growth of 52.96 gr. The results of the analysis of variance on the growth of white snapper showed that the calculated F value was greater than the F table. The water temperature range during the study was in the optimal range, namely 26-30°C, water salinity was around 28-30 ppt, and water pH was around 7.5-7.7.